Recurrent Tako-Tsubo Syndrome following repeated similar road traffic accidents - Cahill, Maeve; Pate, Gordon (Journal of Cardiovascular Medicine and Cardiology, 2020)
Tako-Tsubo Syndrome (TS) is a reversible cardiomyopathy that typically affects women with a history of anxiety, who have experienced a stressful event up to five days prior to presentation. We present the case of a woman who presented with recurring episodes of TS following two near-identical road traffic accidents, four years apart, including multiple imaging modalities.